2023
DOI: 10.1186/s12884-023-05366-2
|View full text |Cite
|
Sign up to set email alerts
|

Harmonization of maternal balanced energy-protein supplementation studies for individual participant data (IPD) meta-analyses – finding and creating similarities in variables and data collection

Abstract: Background Public health and clinical recommendations are established from systematic reviews and retrospective meta-analyses combining effect sizes, traditionally, from aggregate data and more recently, using individual participant data (IPD) of published studies. However, trials often have outcomes and other meta-data that are not defined and collected in a standardized way, making meta-analysis problematic. IPD meta-analysis can only partially fix the limitations of traditional, retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…However, additional research is necessary to clarify the BEP supplement composition needed to achieve positive maternal and child health outcomes, which pregnant women would benefit from such intervention, and the comparison group (only half the studies indicated giving iron or iron being part of antenatal care). In response to this need, a prospective, individual participant data meta-analysis is underway and will include new ongoing or recently completed BEP trials only, which are all compared with IFA [ 54 ]. As part of this work, BEP supplementation given in lactation will also be examined ( https://osf.io/9nq7z ).…”
Section: Review Of the Evidencementioning
confidence: 99%
“…However, additional research is necessary to clarify the BEP supplement composition needed to achieve positive maternal and child health outcomes, which pregnant women would benefit from such intervention, and the comparison group (only half the studies indicated giving iron or iron being part of antenatal care). In response to this need, a prospective, individual participant data meta-analysis is underway and will include new ongoing or recently completed BEP trials only, which are all compared with IFA [ 54 ]. As part of this work, BEP supplementation given in lactation will also be examined ( https://osf.io/9nq7z ).…”
Section: Review Of the Evidencementioning
confidence: 99%
“…While the main effect for SGA was a 3.1% pp reduction, the confidence intervals were wide (− 7.4, 1.2), suggesting a range of treatment efficacy possibilities. Harmonization of data across five pregnancy trials will provide additional evidence on the effects of enhanced BEP supplementation on birth outcomes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new formulation for BEP was proposed through an expert consultation for a ready-to-use BEP, fortified with micronutrients and low-dose calcium and with adequate energy (250–500 kcals) to meet the increased requirements during pregnancy and 14–18 g of high quality protein [ 31 ]. This product formulation is being tested in a number of trials in LMICs [ 32 ]. Thus, we are conducting a cluster-randomized controlled trial in rural Bangladesh to test the enhanced BEP product versus MMS as standard of care in this study area, both by applying a targeted and untargeted approach to examine their effectiveness on increasing birth weight and reducing SGA.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the included trials have some differences in study design, data definitions, and data collection methods. Substantial efforts were made later to harmonize the primary and secondary outcome measures, in our case, through the BEP Initiative (13). Last, studies also differ in eligibility criteria, and one study only enrolled women that were undernourished.…”
Section: Discussionmentioning
confidence: 99%
“…The panel also recommended that BEP products be developed and evaluated in both pregnant and lactating women in low-resource settings to assess health benefits. To further advance the evidence-based research, BMGF funded several independent RCTs and in 2020, convened the Maternal Nutrition Harmonization Workshop to harmonize key variables across these trials and prioritize outcomes for the IPD meta-analysis (13). This later led to the formation of the Maternal BEP Studies Harmonization Initiative (hereinafter BEP Initiative) to examine the pooled effect of BEP in pregnancy and lactation on maternal and child health.…”
Section: Introductionmentioning
confidence: 99%